1990
DOI: 10.1016/0020-7292(90)90209-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin: A new circulating marker of hydatidiform mole?

Abstract: 103 to 32-6x 103), they remained far higher than in non-pregnant women. Serum follicle stimulating hormone concentrations remained suppressed.Conclusions-In this small study serum inhibin concentrations higher than those found in the early follicular phase one to two weeks after evacuation of a hydatidiform mole seemed to be specific for persistent trophoblastic disease. Further data are needed to confirm these promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
15
1
Order By: Relevance
“…Increased levels of circulating inhibin have previously been reported in molar pregnancy, and inhibin concentrations have been suggested to be a marker of hydatidiform mole (HM) [1,2]. However, inhibin assays used in these studies could not differentiate circulating inhibin forms.…”
Section: Introductioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Increased levels of circulating inhibin have previously been reported in molar pregnancy, and inhibin concentrations have been suggested to be a marker of hydatidiform mole (HM) [1,2]. However, inhibin assays used in these studies could not differentiate circulating inhibin forms.…”
Section: Introductioncontrasting
confidence: 42%
“…While the pro-·C ELISA detects a range of inhibin · subunit-containing molecules including some forms of inhibin-A and inhibin-B dimer, it is considered likely that the major inhibin form detected by this assay is free ·-subunit. The increased inhibin level previously found in molar pregnancy [1,2] might have reflected an increase of the free ·-subunit. In early pregnancy in normal women, the major source of inhibin A is the fetoplacental unit [3,10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies indicated that inhibin and activin are expressed in a wide variety of tissues and have a critical role in growth and developmental mechanisms, modulating the proliferation and differentiation of several cell types (2,3). The expression and secretion of inhibin and related proteins in various tumours is currently under investigation (4)(5)(6)(7)(8)(9)(10). The tumoral secretion of inhibin and activin into systemic circulation is suggested by the high serum levels of immunoreactive inhibin in women with ovarian or placental carcinoma (4,5), and by the high levels of serum activin A associated with solid tumours (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, serial measurement of inhibin has been suggested as a marker of follicular development in In Vitro Fertilization program (Tsuchiya et al 1989) and as a tumor marker viz, in hydatidiform mole (Yohkaichiya et al 1989) or granulosa cell tumor (Lappoehn et al 1989).…”
mentioning
confidence: 99%